Effectiveness of local injection of autologous blood versus corticosteroid in treatment of tennis elbow (Journal of Kathmandu Medical College, 2022)
Background: Tennis elbow or lateral epicondylitis is characterised by pain and tenderness at the lateral epicondyle of humerus. There are various treatment modalities recommended, but there is no universally accepted therapeutic modality yet. Objectives: To compare the functional outcomes of local injection of corticosteroid versus autologous whole blood for tennis elbow. Methods: This was a non-randomised trial conducted from May 2020 to January 2021 after ethical clearance. Patients attending orthopaedic surgery outpatient department, Kathmandu Medical College with lateral epicondylitis of the humerus were included by convenience sampling into corticosteroid group or autologous blood injection group based on whether they presented on odd or even calendar days respectively. There were 38 patients in corticosteroid group and 36 patients in autologous blood group. The visual analogue scale (VAS) and Nirschl staging system were calculated before injection, and then at one week, six weeks, and six months after injection. Results: Patients in both groups showed statistically significant decrease in pain from preinjection scores on both VAS and Nirschl scale at all follow-ups. There was no statistically significant difference between the two groups up to six weeks. At six months, autologous blood injection group showed statistically significant decrease in pain compared with corticosteroid injection group on both scoring systems. Conclusion: Both groups showed comparable improvement up to six-week follow-up. Autologous blood injection group had significantly better improvement at six months. Autologous blood injection was more effective than corticosteroid injection at midterm follow-up, and had lower recurrence rate.